ANALISIS MANAJEMEN RISIKO KEUANGAN TERHADAP KONDISI EKONOMI NASIONAL: STUDI STRATEGI PERTAHANAN DAN PENGENDALIAN RISIKO PADA PERUMDA AIR MINUM DUASUDARA KOTA BITUNG - Marco, Malamtiga; Jesika Mamahit; Meyvi I. Susanto; Shendy M. Tahulending; Valensia J. Maria; Monika I. K. Sukatno; Feiby N. Wantah (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2024)
This study analyzes financial risk management implementation at Perumda Air Minum Duasudara Bitung amid national economic uncertainty. The company faces external risks from inflation and macroeconomic downturn, causing increased operational costs and cash flow disruptions with a 60% collection rate. Multi-layered defense strategies include reserve fund formation, regulatory tariff adjustments, and operational efficiency through 50% chemical reduction without quality compromise. Risk control operates systematically via annual planning, prospective identification, and evidence-based decision-making with calculated risk principles. Implementation involves all organizational levels through participatory approaches combining bottom-up input and top-down direction. A qualitative method was employed through interviews with key informants, with data analysis following the Miles and Huberman model involving data reduction, display, and conclusion verification. The research findings indicate that strategies are moderately effective in maintaining stability, though implementation reaches only 60-70% due to regulatory constraints, customer behavior, and internal adaptation delays. Perumda Air Minum Duasudara Bitung has implemented the ISO 31000 and COSO ERM framework approaches, but requires improvements to close the 30–40% implementation gap in order to enhance organizational resilience.